2019
DOI: 10.1007/s40200-019-00468-1
|View full text |Cite
|
Sign up to set email alerts
|

DM-calendar app as a diabetes self-management education on adult type 2 diabetes mellitus: a randomized controlled trial

Abstract: Purpose Era Disruption 4.0 demands development in the management of Diabetes Mellitus (DM) by using application-based intervention that can facilitate nursing intervention. The aim was to evaluate the effect of diabetes mellitus calendar app as a Diabetes Self-Management Education (DSME) program on self-efficacy, HbA1c levels, lipid profile, and insulin in adult type 2 diabetes mellitus (T2DM). Methods It was randomized experimental designsimple random sampling used with a total sample of 30 respondents. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 29 publications
0
34
0
2
Order By: Relevance
“…In total, we included 27 papers analyzing 1646 patients in the intervention groups and 1241 in the control groups. Of the 27 papers, 7 were focused on T1DM (308 patients in the intervention groups and 129 patients in the control groups) [43][44][45][46][47][48][49], 12 were focused on T2DM (743 patients in the intervention groups and 645 patients in the control groups) [50][51][52][53][54][55][56][57][58][59][60][61], and 4 were focused on GDM (339 patients in the intervention groups and 343 patients in the control groups) [62][63][64][65]. The remaining 4 papers did not specify the type of DM they looked at or included a mix of DM types (256 patients in the intervention groups and 124 patients in the control groups) [66][67][68][69].…”
Section: Overviewmentioning
confidence: 99%
See 4 more Smart Citations
“…In total, we included 27 papers analyzing 1646 patients in the intervention groups and 1241 in the control groups. Of the 27 papers, 7 were focused on T1DM (308 patients in the intervention groups and 129 patients in the control groups) [43][44][45][46][47][48][49], 12 were focused on T2DM (743 patients in the intervention groups and 645 patients in the control groups) [50][51][52][53][54][55][56][57][58][59][60][61], and 4 were focused on GDM (339 patients in the intervention groups and 343 patients in the control groups) [62][63][64][65]. The remaining 4 papers did not specify the type of DM they looked at or included a mix of DM types (256 patients in the intervention groups and 124 patients in the control groups) [66][67][68][69].…”
Section: Overviewmentioning
confidence: 99%
“…In total, 743 patients in intervention groups and 645 patients in control groups were investigated in the studies focused on T2DM. Eleven of the studies reported a decrease of HbA 1c within the app intervention groups, yielding a mean difference of -0.42% [50][51][52][54][55][56][57][58][59][60][61], but only 1 study reported a significant change of -1.1% (P<.001) [56]. The proportion changes when differences between intervention and control groups were considered.…”
Section: Hba 1cmentioning
confidence: 99%
See 3 more Smart Citations